Native American America : North America before 1492 - McNeese, Tim (Movements and moments that changed America., 2021)
Investigates the history and culture of Native Americans before European colonists came across the Atlantic. Discusses how most historians think Native peoples came across from Asia over what is now the Bering Sea, how they survived searching for food in the New World, and how Native Americans spread out north, south, east, and west. Includes a glossary.